PSV-40 Antibacterial activity of sodium chlorate and essential oils against Escherichia coli (F18 and K88) during incubations with porcine fecal bacteria. (5th December 2019) - Salinas-Chavira, Jaime; Anderson, Robin; Latham, Elizabeth; Cabrera, Rafael; Castillo, Yamicela; Olivas-Palacios, Ana Luisa; Felix-Portillo, Monserrath; Armendariz-Rivas, Ruth Lisbeth; Arzola-Rubio, Alejandro; Arzola, Claudio
Abstract: In two trials was evaluated the influence of sodium chlorate (SC) and essential oils (EO) on the growth of Escherichia coli F18 and K88 (F18 and K88) incubated with porcine fecal bacteria. The treatments were 2 levels of SC (0 and 10 mM/mL) and 2 levels of Activo® (0 and 1.5%; vol/vol). Activo® (EW Nutrition, Des Moines, IA) is a blend of oregano oil and cinnamon oil (EO) with water and citric acid. In trial one, ½-strength Mueller Hinton broth mixed with porcine feces (0.5% w/vol) was inoculated with a novobiocin and naladixic acid resistant F18-strain. This fecal suspension was transferred to tubes (3/treatment) and anaerobically incubated at 39 o C for enumeration at 0, 6 and 24 h using MacConkey agar supplemented with novobiocin and naladixic acid with aerobic incubation at 37 o C. An interaction (EO x SC) at 6 and 24 was observed (P < 0.01). At 6 and 24 h, EO alone or combined with SC had the lowest counts of F18 (P < 0.05); SC alone had lower counts of F18 than control (P < 0.05). In trial 2 were used the same procedures of trial 1, except that K88 was inoculated in the porcine fecal suspension. There was an interaction at 6 h (P < 0.01) where EO had the lowest counts of K88. The control showed the highest counts of K88 (P < 0.05). There was no interaction at 24 h (P = 0.14). The counts of K88 were reduced by EO (P < 0.01), however the counts were not affected by SC (P = 0.14). It was concluded that SC reduced the counts of E. coli F18, but it had minimal effect on E. coli K88 in the challenged porcine feces; essential oils were effective to reduce the pathogenic bacteria in the porcine feces.